Caregivers' quality of life and psychological health in response to functional, cognitive, neuropsychiatric and social deficits of patients with brain tumour: protocol for a cross-sectional study. Issue 10 (22nd October 2017) - Ramirez, Carole; Christophe, Véronique; Dassonneville, Charlotte; Grynberg, Delphine
Abstract : Introduction: Patients with gliomas generally present cognitive, neuropsychiatric and functional deficits. Although previous research has shown that their caregivers present a poor quality of life and poor mental health, only a few studies have tested in a comprehensive way which deficits/preserved abilities of patients predominantly impact their caregivers. Furthermore, only a few studies have focused on the social impact of gliomas, which may also damage the caregivers' quality of life. Therefore, this cross-sectional study aims to investigate which patients' impairments are particularly deleterious for the caregivers and whether the histological characteristics of the gliomas also affect their quality of life. Methods and analysis: In order to examine these research questions, this study intends to include 180 patients (60 patients with grade II gliomas, 60 patients with grade III gliomas and 60 patients with grade IV gliomas), their caregivers and 60 healthy controls. While patients will complete a full battery of cognitive, neuropsychiatric, functional and social tests, caregivers will complete questionnaires about their quality of life, depression, anxiety and burden. Patients' performances and caregivers' reports of depression and anxiety will be compared with the scores of healthy controls. Eventually, our aim will be to provide specific care support both to reduce patients' deficits and alleviate caregivers' difficulties. Ethics and dissemination: The study has obtained the approval of the local faculty ethics committee ('Comité d'éthique en sciences comportementales'; 2016–5 S41 and 2015–3 S37). On completion of the study, data will be kept by Lille University for 5 years before they are destroyed. Study findings will be disseminated through peer-reviewed journal publications and conference presentations with no reference to a specific individual.